1993
DOI: 10.1093/milmed/158.10.640
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Carcinoma: A Study of Knowledge, Awareness, and Practice of Testicular Self-Examination in Male Soldiers and Military Physicians

Abstract: Multiple-choice questionnaires devised to evaluate knowledge and awareness of testicular carcinoma and the practice of testicular self-examination (TSE) were distributed to 717 male soldiers and 200 military physicians in the Israeli army. Twenty-one percent of the soldiers had received explanations about the importance of TSE; 16% actually received instruction on TSE; yet only 2% practiced TSE regularly. Seventy percent of physicians had been taught how to examine testicles, but only 10% of physicians examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
29
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 0 publications
0
29
1
1
Order By: Relevance
“…10 Thirty percent of male soldiers were aware of their risk of testicular cancer, 16% were taught TSE, and only 2% performed it regularly. 2 Soldiers were 7 times more likely to perform TSE when they were taught the technique. 2 Similar studies have found equally discouraging results.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…10 Thirty percent of male soldiers were aware of their risk of testicular cancer, 16% were taught TSE, and only 2% performed it regularly. 2 Soldiers were 7 times more likely to perform TSE when they were taught the technique. 2 Similar studies have found equally discouraging results.…”
mentioning
confidence: 93%
“…2 Soldiers were 7 times more likely to perform TSE when they were taught the technique. 2 Similar studies have found equally discouraging results. 7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Singer et al 2 reported that only 70% of the military physicians were ever taught how to examine testes, and 10% examined testes as part of a routine physical examination.…”
mentioning
confidence: 93%
See 3 more Smart Citations